2022
DOI: 10.1101/2022.12.11.519957
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Resurrection of plant disease resistance proteins via helper NLR bioengineering

Abstract: Parasites counteract host immunity by suppressing helper NLR proteins that function as central nodes in immune receptor networks. Understanding the mechanisms of immunosuppression can lead to strategies for bioengineering disease resistance. Here, we show that a cyst nematode virulence effector binds and inhibits oligomerization of the helper NLR protein NRC2 by physically preventing intramolecular rearrangements required for activation. A single amino acid polymorphism at the binding interface between NRC2 an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(30 citation statements)
references
References 56 publications
1
29
0
Order By: Relevance
“…Examples of effector targeting NLR come from the P. infestans effector AVRcap1b and the cyst nematode effector SS15, which suppress Solanaceae-specific helper NLRs NRC2 and NRC3 either by affecting their negative regulator NbTOL9a or by preventing their oligomerization and activation 22,23 . We add to these insights, by revealing not only that helper NLRs ADR1-L1 and ADR1-L2 are targeted by P. syringae effector AvrPtoB, but also that AvrPtoB-induced degradation of ADR1-L1 and ADR1-L2 is monitored by the sensor NLR SNC1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Examples of effector targeting NLR come from the P. infestans effector AVRcap1b and the cyst nematode effector SS15, which suppress Solanaceae-specific helper NLRs NRC2 and NRC3 either by affecting their negative regulator NbTOL9a or by preventing their oligomerization and activation 22,23 . We add to these insights, by revealing not only that helper NLRs ADR1-L1 and ADR1-L2 are targeted by P. syringae effector AvrPtoB, but also that AvrPtoB-induced degradation of ADR1-L1 and ADR1-L2 is monitored by the sensor NLR SNC1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…either by affecting their negative regulator NbTOL9a or by preventing their oligomerization and activation 22,23 . We add to these insights, by revealing not only that helper NLRs ADR1-L1 and ADR1-L2 are targeted by P. syringae effector AvrPtoB, but also that AvrPtoB-induced degradation of ADR1-L1 and ADR1-L2 is monitored by the sensor NLR SNC1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies on the SS15 effector from the potato cyst nematode Globodera rostochiensis (Derevnina et al, 2021;Contreras et al, 2023a) revealed that SS15 can inhibit cell death triggered by the helper NLRs NRC2 and NRC3, as well as the tomato (Solanum Pathogen effectors can suppress NLR signaling via diverse strategies. Some effectors can target downstream components required for NLR signaling to suppress immune signaling (Table 1) (A), while others can suppress immune responses by directly targeting NLRs (B).…”
Section: Pathogen Suppression Of Nlrs By Direct Inhibitionmentioning
confidence: 99%
“…lycopersicum) helper NLR NRC1 of the solanaceous NRC network (Fig 4C). SS15 acts as a proteinaceous inhibitor, directly binding to the HD1 region of the central NB-ARC domains of the helper NLRs (Derevnina et al, 2021;Contreras et al, 2023a). SS15 was proposed to immobilize a critical "hinge" loop in the NB-ARC domain, preventing intramolecular rearrangements required for activation and resistosome formation.…”
Section: Pathogen Suppression Of Nlrs By Direct Inhibitionmentioning
confidence: 99%